THE ANALYSIS OF FINANCIAL RATIOS EFFECT ON THE STOCK PRICE OF CONSUMER GOODS SECTOR COMPANIES LISTED IN KOMPAS100 INDEX - Imansyah, Shabri; H. Mustafa, Matrodji (Dinasti Publisher, 2021)
This research aims to discern the effect of financial ratios on the stock price of Consumer Goods Industry Sector Companies listed in Kompas 100 Index on 2013-2019 period, partially or simultaneously. The financial ratios analyzed in this research are: Current Ratio (CR), Net Profit Margin (NPM), Return on Equity (ROE) and Dividend Yield (DY). The research population is the Consumer Goods Industry Sector Companies listed in Kompas 100 Index on 2013-2019 period. There are 5 Consumer Goods Industry companies used as the research sample by applying the purposive sampling method. This research uses documentation as the collection data technique as well as a panel data as the data analysis technique. This research shows that NPM variable has a partially positive relationship on the stock price, ROE has a positive relationship on the stock price at a confidence level of 90 percent, while CR and DY have no effects on stock price. The CR, NPM, ROE and DY variables influence the stock price simultaneously. CR, NOM, ROE and DY variables can explain the stock price on the Consumer Goods Industry Sector companies listed in Kompas 100 Index at 98,38%.